Change in psychological distress in longer‐term oesophageal cancer carers: are clusters of illness perception change a useful determinant?. Issue 6 (20th September 2015) - Graham, Lisa; Dempster, Martin; McCorry, Noleen K.; Donnelly, Michael; Johnston, Brian T.
Abstract: Objective: This study provides a longitudinal assessment of distress in longer‐term oesophageal cancer carers, while examining illness perception schema as a possible determinant of change in distress over time. Methods: Oesophageal cancer carers (n = 171), 48 months post‐diagnosis, were assessed at baseline and 12 months later with the Illness Perception Questionnaire‐Revised, Cancer Coping Questionnaire, Hospital Anxiety and Depression Scale and Concerns About Recurrence Scale. Results: Findings report deterioration from normal to probable anxiety in 35.7% of carers and probable depression in 28.7% carers over time. Fear of recurrence remained stable. Changes in control, consequence and cause beliefs were identified as key determinants of a change in psychological morbidity. Conclusions: Illness beliefs appear to be valuable targets for psychological intervention to improve wellbeing among carers of people with oesophageal cancer. Copyright © 2015 John Wiley & Sons, Ltd.